2018
DOI: 10.1002/jee.20235
|View full text |Cite
|
Sign up to set email alerts
|

The Popularity and Intensity of Engineering Undergraduate Out‐of‐Class Activities

Abstract: Background Although researchers have documented the outcomes of various out‐of‐class activities for undergraduate students, less attention has been given to student perspectives on activity category and activity levels, particularly when considering demographics such as gender and race/ethnicity. Purpose/Hypothesis This study aims to create a more nuanced profile of engineering undergraduate engagement in out‐of‐class activities disaggregated by gender, race/ethnicity, and level of activity. As an exploratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…Similarly, in reviewing literature on students' out-of-class involvement, Simmons et al [13] found that academic activities were associated more with career and professional development, while non-academic activities were associated with academic and social engagement outcomes. These findings on perceived development are further supported by Simmons et al's [65] survey of 816 undergraduate engineering students. These engineering students reported that the primary reasons for their participation in student organizations were to fulfill personal interests and to gain experiences.…”
Section: Rq1supporting
confidence: 63%
See 1 more Smart Citation
“…Similarly, in reviewing literature on students' out-of-class involvement, Simmons et al [13] found that academic activities were associated more with career and professional development, while non-academic activities were associated with academic and social engagement outcomes. These findings on perceived development are further supported by Simmons et al's [65] survey of 816 undergraduate engineering students. These engineering students reported that the primary reasons for their participation in student organizations were to fulfill personal interests and to gain experiences.…”
Section: Rq1supporting
confidence: 63%
“…Beyond the extent of involvement in student organizations and the types of activities in which students participate through these organizations, some studies have examined the types of organizations in which students are involved. These classifications range from broad categories of academic versus non-academic organizations [26], [34] to detailed lists of 6-20+ varieties of involvement (e.g., pre-professional, service, music, culture) [29], [42], [65], [66]. Holzweiss, Rahn, & Wickline [34] investigated students' motivation for participating in academic versus non-academic student organizations and the benefits they perceived from their involvement.…”
Section: Rq1mentioning
confidence: 99%
“…They feel confident in their abilities, feel as smart as others, but feel worried about how they are perceived by others and self-conscious in social settings. Although the need for social support was not found to be significant for these groups, they can benefit from participation in design competition teams and experiential learning [32]. Practical applications of jjjj prior studies and the results of our study demonstrate that core features of the CAMP-YES program --experiential learning, mentoring, and group activities that promote a "sense of community and inclusiveness"--is one example of a program design based on sound, theoretical foundations.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, students who report higher levels of social integration are more likely to have higher GPAs, especially significant for female students [30,31]. Practical applications from the preliminary findings of our study show that college campus social environments in which North American, female students can thrive should include opportunities that promote engagement such as community service, experiential learning, living-learning jjjj communities, major-related organizations and groups, and engineering outreach support [30,32].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation